Comparison of the physical, physiological, and psychological responses of the high-intensity interval (HIIT) and small-sided games (SSG) training programs in young elite soccer players - Ouertatani, Z.; Selmi, O.; Marsigliante, S.; Aydi, B.; Hammami, N.; Muscella, A. (International Journal of Environmental Research and Public Health, 2022)
We investigated the effects of high-intensity interval (HIIT) and small-sided games (SSG) training programs on physiological and psychological responses in young soccer players. Twenty-four male soccer players (age 16.7 ± 0.9 years) were divided into two groups (HIIT and SSG) and completed a 6-week training programs consisting of two training sessions a week. HIIT consisted of intermittent runs lasting 15 s at the 110% maximum aerobic speed followed by a passive recovery lasting 15 s; SSG was instead structured in a 4 versus 4 players games on a playing field of 25 × 35 m. The muscular power of the lower body was assessed before and after each training session using the 5-jump test to leg length, and two incremental field tests (VAMEVAL test and modified agility t-test). Our results show that HIIT and SSG have similar beneficial effects on the variables connected to the soccer-specific performance and the endurance with little influence on neuromuscular performances. Psychological responses were assessed using the "physical activity enjoyment scale", the Hooper index and the POMS variables. Results showed that SSG offers greater perceived enjoyment than what can be achieved with HIIT. In conclusion, SSG can be considered an effective, more motivating, and fun soccer-specific training that brings about physiological responses and neuromuscular adjustments in young soccer players.